Analyzing the Impact of Derivatives on the Emerging Markets Financial Stability - Scholer-Iordanashvili, Lela (European Scientific Journal, ESJ, 2020)
In recent decade, volatility of stocks and interest rates, together with the globalization of capital markets, increased the demand on financial instruments with the purpose of distribution of risks. The estimation of the role of financial derivatives instruments is very important for the stability of international financial system. The impact of derivatives upon International Financial Crises is an issue that is still dividing academics and practitioners. This paper focuses on analyzing the roles of derivatives in the financial crises. Within the framework of this research, three (3) emerging countries were studied for 1997-2010 quarterly. OLS regressive equation was used for empirical tests. The model includes the following variables: crisis index (dependent variable) and independent variables which include: the Ratio of the Current Account to GDP, the Ratio of the Domestic Credits on Private Sector to GDP, and the Ratio of the total notional amounts outstanding of the exchange traded derivatives to Foreign Exchange Reserves. Empirical analysis shows that the influence of derivatives over financial stability is not unilateral, and it depends on the characteristics of the financial system of the country. The study conducted on example of emerging markets, particularly Argentina, Russia and Brazil, revealed negative influence of derivatives on the financial system.